Lichenoid lesions of the upper lip: A retrospective study of 24 cases - Katsoulas, Nikolaos (Med Oral Patol Oral Cir Bucal, 2018)
BACKGROUND: Lichenoid lesions of the upper labial mucosa, without other oral or extraoral manifestations seem to be rare. The clinicopathologic features of 24 such cases are presented and the pertinent literature is reviewed. MATERIAL AND METHODS: 24 Caucasian patients that clinically presented lichenoid features on the upper labial mucosa, with or without lichenoid lesions on the adjacent gingiva, were included in the study. Clinical features were extracted from the patients’ records, while dental plaque/calculus accumulation and composite resin restorations of the adjacent teeth were recorded. Four cases where an incisional biopsy was performed were further evaluated. RESULTS: There were 8 males and 16 females, with a mean age of 62.7 years. 64.2% were under hypertensive therapy. In 13 cases gingival involvement was noticed, 16 cases exhibited calculus deposition, while 6 cases presented with composite resin fillings of the adjacent teeth. In 4 cases an incisional biopsy was performed showing features of lichenoid reaction. In 37.5% significant improvement was observed after topical treatment with corticosteroids and antimicrobial agents. CONCLUSIONS: Lichenoid lesions of the upper lip may represent a distinct variety of oral lichenoid lesions, but as the number of cases reported so far is too small for definite conclusions on pathogenesis and management to be made, a long-term follow-up is mandatory. Key words:Lichenoid lesions, upper lip, oral lichen planus, lichenoid reactions.